2005
DOI: 10.1007/s10534-005-3686-x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, the Pancreas, and Diabetes: Insights from Rodent Studies and Future Directions

Abstract: Molecular and cellular studies have demonstrated several roles for zinc (Zn) in insulin production and the consequent actions of insulin on metabolism. Clinical and epidemiological studies suggest that reduced Zn status is associated with diabetes. Investigations of Zn in rodent models of diabetes have provided a valuable link for understanding the molecular, cellular, clinical and epidemiological observations in the context of inter-organ metabolism and the metabolic disturbances of diabetes. This review high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
127
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(130 citation statements)
references
References 61 publications
(63 reference statements)
0
127
0
3
Order By: Relevance
“…The role of Zn in the pancreas and diabetes based on rodent studies and experimental manipulations of Zn have been described. 29,30 Zn deficient has been linked to the diabetes mellitus in experimental and clinical studies. [31][32][33] In Zn deficiency rats, they were found that pancreatic zinc levels and serum insulin levels were significantly decreased, and glucose intolerance was increased.…”
Section: Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Zn in the pancreas and diabetes based on rodent studies and experimental manipulations of Zn have been described. 29,30 Zn deficient has been linked to the diabetes mellitus in experimental and clinical studies. [31][32][33] In Zn deficiency rats, they were found that pancreatic zinc levels and serum insulin levels were significantly decreased, and glucose intolerance was increased.…”
Section: Zincmentioning
confidence: 99%
“…Zn supplementation has been shown to be effective for preventing or ameliorating diabetes in several rodent models of type 1 and type 2 diabetes. 29,30 The epidemiological evidences, associating diabetes with Zn deficiencies, have also indicated the effects of Zn and associated metallothionein (MT) on reducing diabetic complications associated with oxidative stress. 30 Moreover, it has been suggested that the Zn transporter ZnT-8 is a key protein for both zinc accumulation and regulation of insulin secretion in pancreatic β-cells.…”
Section: Zincmentioning
confidence: 99%
“…Under these conditions, we achieved highly selective sulfonation only at the para-positions of the three phenyl rings having no attached amino group. The water-soluble product, 2NH 2 -TPPS 3 (6) [where TPPS 3 is 5-phenyl-10,15,20-tris(4-sulfonatophenyl)porphine], was purified by reversephase column chromatography (RP-18). The zinc-binding units were then installed to give 1 by reductive amination of 6 in the presence of compound 7, which converts to its ring-opened aldehyde form 8 upon raising the pH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although most forms of biological zinc are tightly bound and serve as essential structural and catalytic components of metalloprotein scaffolds (3), mobile zinc pools are present in certain mammalian organs, including the brain (4), retina (5), pancreas (6), and prostate (7). The static and kinetic equilibria of these ''mobile'' zinc pools are under strict regulation for maintenance of their physiological roles (8,9).…”
mentioning
confidence: 99%
“…Zinc plays important roles in various biological processes, such as gene transcription [1] and metalloenzymes [2], and is involved in both extra-and intra-cellular functions. However, irregular intake of Zn 2+ can cause Alzheimer's disease [3][4][5] and Parkinson's disease [6].…”
Section: Introductionmentioning
confidence: 99%